2020
DOI: 10.1039/d0ra03045g
|View full text |Cite
|
Sign up to set email alerts
|

The aging properties and phase morphology of silica filled silicone rubber/butadiene rubber composites

Abstract: Relationship between the aging properties and phase morphology of silica filled silicone rubber (VMQ)/butadiene rubber (BR) composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The change of material modulus of elasticity means the molecular chain inside the rubber will deform with the rubber aging process and the external kinetic energy is converted into the friction energy inside the rubber to offset it. As the lifespan increases, the rubber spring will undergo an oxidative degradation reaction or a structuring reaction 39 . This directly leads to a decrease in the relative molecular weight of the rubber spring, a decrease in strength, and surface hardening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of material modulus of elasticity means the molecular chain inside the rubber will deform with the rubber aging process and the external kinetic energy is converted into the friction energy inside the rubber to offset it. As the lifespan increases, the rubber spring will undergo an oxidative degradation reaction or a structuring reaction 39 . This directly leads to a decrease in the relative molecular weight of the rubber spring, a decrease in strength, and surface hardening.…”
Section: Resultsmentioning
confidence: 99%
“…As the lifespan increases, the rubber spring will undergo an oxidative degradation reaction or a structuring reaction. 39 This directly leads to a decrease in the relative molecular weight of the rubber spring, a decrease in strength, and surface hardening. Due to these changes, the simulation result shows that the vertical and horizontal deformation of the rubber spring decreases as the aging time increases.…”
Section: Determination Of Detection Locationmentioning
confidence: 99%
“…Δ S ″ reflects the crosslinking degree of the polymer. [ 23 ] It is indicated that the addition of SR increases the crosslinking density of SR/EPDM blends, which is beneficial to the improvement of the strength and mechanical properties of the blends.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they appear as two important materials on which intensive work has been done. Corresponding to this, Leng et al [5] found that after thermal oxidative aging, the physical properties retention rate of VMQ/BR (butadiene rubber) are higher than that of BR. In case of CR compound [6], the dependence of tensile strength on the crosslinking time and temperature shows that the influence of crosslinking time is such that in the range between 4.75 min and 5.5 min, the tensile strength value reaches the maximum and then declines dramatically.…”
Section: Introductionmentioning
confidence: 88%